Ways to Improve Tax Control and its Regulation - o’g’li, Turaev Alijon Akmal (Research Parks Publishers, 2023)
In this article, the importance of in-house inspections is important in increasing the share of budget revenues in the country through the correct calculation and timely payment of mandatory payments to the state budget through the control of business entities on the basis of tax legislation. In addition, the views and opinions of economists on tax control have been studied and detailed comments have been made on their views. Within the framework of tax control, the content of the in-house tax audit, the order of its conduct, the importance of the organization and its specific features were analyzed.